2020
DOI: 10.22490/24629448.3700
|View full text |Cite
|
Sign up to set email alerts
|

Actividad in vitro de los extractos etanólicos de Lantana camara L., Petiveria alliacea L. y Lippia dulcis T. frente a bacterias patógenas

Abstract: Introducción. La biodiversidad colombiana y los saberes tradicionales permiten la exploración de plantas medicinales con potencial actividad antimicrobiana que podrían usarse para tratamiento de infecciones. Objetivos. Determinar la actividad antibacteriana de extractos etanólicos de Lantana camara L., Petiveria alliacea L. y Lippia dulcis T. sobre Pseudomonas aeruginosa ATCC 9027, Escherichia coli ATCC 25922, Proteus vulgaris ATCC 6380 y Staphylococcus aureus ATCC 25923. Materiales y métodos. Se reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…The aqueous extract of Lantana camara, at concentrations of 25 and 50 mg/ml, showed bactericidal activity on the growth of P. celebensis. These results corroborate those of Navarrete et al [29], who showed that the aqueous extract of Lantana camara was bactericidal against Staphylococcus aureus an also of the fact that they are of different concentration and chemical composition [30].…”
Section: Effect Of Plant Extracts On the Inhibition Zone Diameter Of ...supporting
confidence: 91%
See 1 more Smart Citation
“…The aqueous extract of Lantana camara, at concentrations of 25 and 50 mg/ml, showed bactericidal activity on the growth of P. celebensis. These results corroborate those of Navarrete et al [29], who showed that the aqueous extract of Lantana camara was bactericidal against Staphylococcus aureus an also of the fact that they are of different concentration and chemical composition [30].…”
Section: Effect Of Plant Extracts On the Inhibition Zone Diameter Of ...supporting
confidence: 91%
“…The results obtained with Lantana camara on the development of R. solanacearum are similar to those of Bashir et al[27], who showed that the flavones extracted from the methanol extract of dried leaves of L. camara also showed the antibacterial and antifungal properties which inhibited the development of Colletotrichum gloeosporioides Penz the causal agent of Anthracnose disease of mango fruits. Similar results were reported by Navarrete et al[28], who showed that ethanolic extracts of Lantana…”
supporting
confidence: 91%